HUBUNGAN PERAN KELUARGA DALAM MERAWAT LANSIA DENGAN INTENSITAS TEKANAN DARAH DI DUSUN JOGODAYO JABON KECAMATAN MOJOANYAR KABUPATEN MOJOKERTO - Rifaatul laila Mahmudah; Zaenal Efendi (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2021)
High blood pressure is a risk factor for stroke, heart attack, heart failure and arterial aneurysm, and is a major cause of chronic heart failure. The study design using analytic cross sectional study. The population in this study were 21 respondents who once used as a sample to the sampling technique total sampling. The instrument used in this study is a questionnaire. Family roles research results indicate that the majority of respondents are negative role of the family as many as 12 respondents (57.1%). The intensity of blood pressure showed at most down as many as 8 respondents (38.1%). Cross tabulation shows the most is the respondents who have a positive family role and the intensity drop in blood pressure that is as much as 8 respondents (38.1%). Spearman rho correlation test results obtained Asymp.Sig value of 0.000, which means there is a relationship role of the family in caring for the elderly with the intensity of the blood pressure in the hamlet village Jogodayo Jabon Mojoanyar District of Mojokerto. Family roles affect blood pressure decrease in the intensity of the respondents. Family nursing task is to provide facilities, equipment and support to the elderly to maintain blood pressure by providing facilities, providing information, encouragement and motivation to the elderly to maintain blood pressure.